Menjawab Keraguan Maurice Bucaille tentang Kesesuaian Hadis dan Sains - Ahmad Fudhail (Refleksi, 2020)
This article attempts to criticizes the thoughts of Maurice Bucaille, an Orientalist from France who doubts the authenticity of the hadits contained in the book Ṣaḥīḥ al-Bukhārī, especially those relating to medicine. As the primary sources that author uses, the Book of La Bible, Le Coran, et La Science which has been translated into Indonesian by M. Rasyidi with the title Bibles, Quran, and Modern Science. This research seeks to examine and examine the thinking of Maurice Bucaille and then analyze the traditions that are doubtful of their authenticity with a medical science approach. The hadits that are authenticated by Maurice Bucaille -ḥadīth about the development of human embryos, hadits about flies, hadits about the usefulness of dates, and hadits about fever- are authentic hadits seen from a medical perspective.  In other words, the hadits is in accordance with modern science. This proves that the criticism shown by Maurice Bucaille is incorrect.